Sosialisasi Pemilihan Makanan Sehat Untuk Mencegah Obesitas Pada Siswa Smpn 1 Darul Imarah - Serly Nurfajri Erwiyanti; Maulinasari; Naufal Abdi; Dharina Baharuddin (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
Adolescent obesity is a growing health problem in Indonesia, particularly among children aged 13–15. Consuming foods high in sugar and fat without adequate nutrition education is a major contributing factor. This community service activity aims to increase students’ knowledge about the importance of choosing healthy foods as a preventative measure for obesity. The activity was conducted at SMPN 1 Darul Imarah, involving 14 ninth-grade female students. The methods used were interactive lectures, group discussions, healthy food selection exercises, and pre- and post-test evaluations. The evaluation results showed an increase in the average score from 82.86 to 92.85, with an increase in the high knowledge category from 60% to 93%. There were no more students in the low knowledge category after the intervention. These results indicate that a fun and participatory educational approach can significantly improve students’ nutritional literacy. This type of education needs to be expanded to become part of a sustainable school health program.